A Clinical Study to Assess the Efficacy of Anterior Transarticular C1-C2 Screw Fixation for Stabilization of AtlantoAxial Instability (Medico Legal Update, 2021)
Introduction: The upper cervical spine includes the atlas (C1) and Axis (C2). The anatomy of upper twovertebrae is unique from each other. Atlanto-axial articulation is the most unique, mobile segment of spine,which largely depends on ligamentous supports based on integrity of odontoid for its stability. Historically,atlanto-axial subluxation was treated by reduction and fusion of C1-C2 joint. However, High riding vertebralartery precludes the placement of posterior trans-articular screw, which is liable to injury during screwplacement. Socomputed tomography scans can be used to evaluate the risk of “high riding” vertebral arteryduring the management of atlanto-axial subluxation. Hence, anterior trans-articular screw fixation techniqueavoids the course of high riding vertebral artery.Material and Method: Nine patients underwent NCCT cervical spine with 3-D reconstruction and clinicalevaluation of pain was done by recording the VAS score done pre operatively and after surgery.Results: All surgical cohorts underwent anterior C1-C2 fixation with an average follow up for 24 months.All patients were assessed as per fixed protocol of our local hospital guidelines of orthopaedics department.Pain score was clinically evaluated by VAS score before and after surgery yielding 90% excellent result.Conclusion: Anterior Trans-articular C1-C2 screw fixation isa minimally invasive technique with less bloodloss, shorter skins car and faster post-operative recovery. It is an appropriate technique for stabilization ofAtlanto-Axial instabilities.